2021
DOI: 10.1029/2020gl091991
|View full text |Cite
|
Sign up to set email alerts
|

Smartrock Transport From Seconds to Seasons: Shear Stress Controls on Gravel Diffusion Inferred From Hop and Rest Scaling

Abstract: Our ability to test probabilistic models linking clast movements to bedload diffusion is most limited by basic field data, because measuring transport statistics during natural floods is difficult. We embedded accelerometers and gyroscopes into artificial cobbles, and measured transport during 28 daily snowmelt floods in Halfmoon Creek, Colorado, USA. The tracers captured ≈6 orders of temporal magnitude of rest durations in one data set for the first time. Motions and rests suggest a scaling transition around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…For example, some studies (Heyman et al 2013) have suggested an exponential distribution of resting times and thus a similar entrainment condition to the deposition condition (a Poisson process). As a comparison, there are other studies (Martin et al 2012;Martin, Purohit & Jerolmack 2014;Fraccarollo & Hassan 2019;Liu et al 2019;Pretzlav, Johnson & Bradley 2021) suggesting a power-law-like distribution for the resting times, although a simple form of the entrainment condition is not available yet. It is noted that, by incorporating other physical processes like the burial and exhumation of particles during their streamwise transport (Wu et al 2019a,b), the power-law-like resting time distribution can be recovered which consequently induces the anomalous diffusion of bedload particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some studies (Heyman et al 2013) have suggested an exponential distribution of resting times and thus a similar entrainment condition to the deposition condition (a Poisson process). As a comparison, there are other studies (Martin et al 2012;Martin, Purohit & Jerolmack 2014;Fraccarollo & Hassan 2019;Liu et al 2019;Pretzlav, Johnson & Bradley 2021) suggesting a power-law-like distribution for the resting times, although a simple form of the entrainment condition is not available yet. It is noted that, by incorporating other physical processes like the burial and exhumation of particles during their streamwise transport (Wu et al 2019a,b), the power-law-like resting time distribution can be recovered which consequently induces the anomalous diffusion of bedload particles.…”
Section: Discussionmentioning
confidence: 99%
“…2012; Martin, Purohit & Jerolmack 2014; Fraccarollo & Hassan 2019; Liu et al. 2019; Pretzlav, Johnson & Bradley 2021) suggesting a power-law-like distribution for the resting times, although a simple form of the entrainment condition is not available yet. It is noted that, by incorporating other physical processes like the burial and exhumation of particles during their streamwise transport (Wu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that bedload transport depends on flow strength and is highly stochastic (Ancey, 2010; Ancey et al., 2008; Einstein, 1937, 1950; Gomez et al., 1989; Hassan et al., 1991; Paintal, 1971; Pierce & Hassan, 2020b; Singh, Fienberg, et al., 2009; Singh, Lanzoni, & Foufoula‐Georgiou, 2009; Singh et al., 2010). Although several proposed theories of stochastic sediment transport have reproduced a number of statistical properties of bedload transport and particle movement (Ancey, 2010; Ancey et al., 2008; Church & Hassan, 1992; Einstein, 1937, 1950; Furbish et al., 2012; Ganti et al., 2009, 2010; Hassan et al., 1991; Paintal, 1971; Pierce & Hassan, 2020a; Pretzlav et al., 2021; Roseberry et al., 2012; Wong et al., 2007), a more rigorous validation of these models is still lacking for the range of transport conditions observed in nature, including a varying hydrograph and evolving bed topography.…”
Section: Introductionmentioning
confidence: 99%
“…During particle movement, the embedded sensors record its acceleration data, which are transformed to the exerted forces by multiplying the particle mass. This new approach has been applied to measurement of impact force of test debris on infrastructures (Shafiei et al, 2016; Spreitzer et al, 2019), monitoring river bed scour and sediment transport (Pretzlav et al, 2020, 2021; Stephenson & Abazović, 2016), and particle entrainment mechanics (AlObaidi & Valyrakis, 2021; Frank et al, 2015; Maniatis et al, 2017, 2020). Use of instrumented accelerometers to measure the inertial forces exerted on target particle is distinctly different from the previously invasive methods.…”
Section: Introductionmentioning
confidence: 99%